2004
DOI: 10.1111/j.1365-2133.2004.06048.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear beta-catenin in basal cell carcinoma correlates with increased proliferation

Abstract: The absence of beta-catenin gene mutations indicate that the Hh pathway-directed Wnt signalling remains the most likely cause of nuclear beta-catenin accumulation in BCC. Additionally, the correlation with increased proliferation is the first evidence that nuclear beta-catenin may have a biological effect. However, a causal link between Hh pathway deregulation, Wnt ligand overexpression, nuclear beta-catenin accumulation and increased proliferation remains to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
87
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 25 publications
8
87
1
4
Order By: Relevance
“…Nuclear b-catenin is increased in human BCCs (El Bahrawy et al, 2003;Saldanha et al, 2004). We stained sections of BCC-like lesions induced by tet on Gli1 (Li et al, 2006) using an antibody to the active, unphosphorylated form of b-catenin.…”
Section: Gli1 Induces the Accumulation Of Transcriptionally Active B-mentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear b-catenin is increased in human BCCs (El Bahrawy et al, 2003;Saldanha et al, 2004). We stained sections of BCC-like lesions induced by tet on Gli1 (Li et al, 2006) using an antibody to the active, unphosphorylated form of b-catenin.…”
Section: Gli1 Induces the Accumulation Of Transcriptionally Active B-mentioning
confidence: 99%
“…In Xenopus animal caps, induction of Wnt8 and Wnt11 is important for Gli2-mediated alteration of the posterior mesoderm (Mullor et al, 2001). Human BCCs have constitutive Shh pathway signaling and show increased levels of Wnt2b and Wnt5a and increased levels of nuclear b-catenin (Bonifas et al, 2001;El Bahrawy et al, 2003;Saldanha et al, 2004;Hooper and Scott, 2005). As observed for Shh pathway genes such as Gli1, b-catenin promotes follicle-like tumors or BCCs in transgenic mice (Alonso and Fuchs, 2003;Nicolas et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, efforts have been focused on the incidence of nuclear accumulation of b-catenin, a hallmark of constitutive activation of Wnt signalling, in BCC tumor samples (Behrens et al, 1996;Huber et al, 1996). However, several such attempts to detect nuclear accumulation of b-catenin have yielded conflicting observations (Boonchai et al, 2000;Yamazaki et al, 2001;El-Bahrawy et al, 2003;Saldanha et al, 2004). To further verify the involvement of Wnt pathway in BCC, we constructed a tissue microarray (TMA) of 75 BCC tumors and corresponding normal skin samples, and analysed these samples for b-catenin expression and Figure 1f).…”
mentioning
confidence: 99%
“…However, several subsequent studies using different antibodies were able to detect nuclear bcatenin in 23-70% of BCC samples (Yamazaki et al, 2001;El-Bahrawy et al, 2003;Saldanha et al, 2004). Although the precise reasons for such discrepancies is not clear, it has been suggested that this could be caused by differences in tissue fixation and processing (Yamazaki et al, 2001;Saldanha et al, 2004).…”
mentioning
confidence: 99%
“…In addition, CTNNB1 mutations are associated with specific cancers. 15,16 Infection data from in vitro and in vivo experiments demonstrated that CTNNB1 shRNA-expressing SL could not only induce potent and specific gene silencing of CTNNB1, c-Myc and cyclin D1, but also promote tumor and polyp regression. Moreover, efficient silencing of CTNNB1 was also obtained in mucosal tissues from APC Min mice after oral administration of SL-pSLS-mCAT.…”
Section: Introductionmentioning
confidence: 99%